Managerial Accounting: concepts and Uses, Second Edition (Book). - Coe, Teddy L.; Meyer, Philip E. (The Accounting Review, 1982)
Reviews the book "Managerial Accounting: Concepts and Uses," 2nd ed., by Rudolph W. Schattke and Howard G. Jensen.